PENGARUH MANAJEMEN DANA, KUALITAS LAYANAN PENDIDIKAN, DAN GAYA KEPEMIMPINAN TERHADAP KEEFEKTIFAN SEKOLAH - Dr. Parwanto, MM (Pusat Standar dan Kebijakan Pendidikan, BSKAP, Kemendikbudristek, 2022)
This study aims to determine the effect of school fund management, quality of service provided by district/city education offices, and principals’ leadership style on school effectiveness. This research used quantitative approach with a structural equation model design. The population of this study were all students from public junior high schools in the region of the former Surakarta Residency. The research sample was determined using area probability sampling. Data were collected through a closed questionnaire utilizing the Likert scale. Data were processed using the Linear Structural Relationship model. The results showed that the theoretical model built on the relevant theory was supported by empirical data. The description of the latent variables of fund management, service quality, leadership style, and school effectiveness showed positive outcomes. In details, the direct effect of a fund management on the school effectiveness was 0.45. This was greater than the indirect effect, which was 0.24 (0.67x0.36). Meanwhile, the direct influence of the service quality of the district/city education offices on the school effectiveness was not significant. However, the indirect influence of a leadership style was quite significant at 0.37. The testing result of the influence of the principal’s leadership style on school effectiveness was quite significant at 0.36 with an error tolerance of 0.05.